Dissecting the Species-Specific Virome in Culicoides of Thrace - Konstantinidis, Konstantinos; Bampali, Maria; de Courcy Williams, Michael; Dovrolis, Nikolas; Gatzidou, Elisavet; Papazilakis, Pavlos; Nearchou, Andreas; Veletza, Stavroula; Karakasiliotis, Ioannis (Frontiers in Microbiology, 2022)
Biting midges (Culicoides) are vectors of arboviruses of both veterinary and medical importance. The surge of emerging and re-emerging vector borne-diseases and their expansion in geographical areas affected by climate change has increased the importance of understanding their capacity to contribute to novel and emerging infectious diseases. The study of Culicoides virome is the first step in the assessment of this potential. In this study, we analysed the RNA virome of all Culicoides species within the geographical area of Thrace in the south-eastern part of Europe, a crossing point between Asia and Europe and important path of various arboviruses. The analysis of the RNA virome of 10 Culicoides species resulted in the identification of the genomic signatures of 14 novel RNA viruses all of which are significantly divergent from previously identified related viruses from the Solemoviridae, Phasmaviridae, Bunyaviridae, Reoviridae, Chuviridae, Partitiviridae, Orthomyxoviridae, Rhabdoviridae and Flaviviridae families. Each Culicoides species carried a species-specific set of viruses some of which are related to viruses from other insect vectors in the same area, contributing to the idea of a virus-carrier web within the ecosystem. The identified viruses not only expand our current knowledge on the virome of Culicoides but also set the basis of the genetic diversity of such viruses in the area of south-eastern Europe. Furthermore, our study highlights the need of such metagenomic approaches to include as many partners as possible of the local virus-carrier web that interact to build and evolve the virome of a geographical area.